Managing slope performance in uncertain geological conditions at Meandu Mine, Queensland - Simmons, J.V.; Edwards, D.C.; Ferdinands, N. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
The Ground Control Management Plan at the Meandu Mine provides the basis for the approval of slope designs and operational activities in a coal deposit sequence characterised by complex sedimentation, thick seams, faults, an eruptive volcanic cover sequence, and multiple episodes of deep weathering. Rapid lateral and vertical variations in geotechnical conditions imply that the overburden model for mine planning includes significant uncertainties for slope hazard and stability risk assessment. The paper provides a description of the evolution of slope designs and circumstances that have shaped the current approach to short-term design and operational hazard management Long-term slope design considerations also include the groundwater regime and the placement of both coal washery tailings and power station ash slurry in mined-out voids.